1993
DOI: 10.1007/bf01709272
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin effect on early and late changes in acute lung injury in sheep

Abstract: Our findings suggest that ASA: 1) is only effective to treat the very transient TxB2-induced pulmonary vasoconstriction resulting in hydrostatic edema, and it is ineffective, even accentuates, the subsequent major pulmonary endothelial cell injury leading to alveolar flooding that is unrelated to TxB2; 2) has a transient protective effect on the TxB2-induced early bronchospasm; 3) has a biphasic behaviour on gas exchange, with a benefit which lasts only one hour and then results in a worse gas exchange; 4) has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…The finding that prehospital aspirin use is associated with a decreased risk of ARDS in critically ill patients is consistent with the known beneficial effects of aspirin in both clinical and experimental acute lung injury (13, 26, 27). In addition, aspirin also has potent effects on treatment and prevention of sepsis via anti-platelet and anti-inflammatory effects in preclinical and clinical studies (28-30).…”
Section: Discussionsupporting
confidence: 82%
“…The finding that prehospital aspirin use is associated with a decreased risk of ARDS in critically ill patients is consistent with the known beneficial effects of aspirin in both clinical and experimental acute lung injury (13, 26, 27). In addition, aspirin also has potent effects on treatment and prevention of sepsis via anti-platelet and anti-inflammatory effects in preclinical and clinical studies (28-30).…”
Section: Discussionsupporting
confidence: 82%
“…No benefit was observed in one study (28) and in one study (29) worsening of inflammation was demonstrated.…”
Section: Resultsmentioning
confidence: 89%
“…In 10 studies the antiplatelet drug was ASA (2631, 3538) in three studies ASA-triggered lipoxin (32, 33, 38) , and in three studies ASA-triggered resolving D 1 (34, 39, 40) were studied. In 12 preclinical studies (2933, 3540) a mouse model was used, in two preclinical studies a sheep model (27, 28) and in one study a dog model (26). Both direct and indirect models of acute lung injury were tested (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations